Pectin as a rheology modifier: Origin, structure, commercial production and rheology - Chan, Siew Yin; Choo, Wee Sim; Young, David James; Loh, Xian Jun (Carbohydrate polymers, 2017)
•The structure – property relationships of pectin polysaccharides are reviewed.•The mechanism of gelling varies with the degree of methylation and other parameters.•The viscoelastic behavior of a pectin gel depends on the gelling mechanism. Pectins are a diverse family of biopolymers with an anionic polysaccharide backbone of α-1,4-linked d-galacturonic acids in common. They have been widely used as emulsifiers, gelling agents, glazing agents, stabilizers, and/or thickeners in food, pharmaceutical, personal care and polymer products. Commercial pectin is classified as high methoxy pectin (HMP) with a degree of methylation (DM) >50% and low methoxy pectin (LMP) with a DM <50%. Amidated low methoxy pectins (ALMP) can be obtained through aminolysis of HMP. Gelation of HMP occurs by cross-linking through hydrogen bonds and hydrophobic forces between the methyl groups, assisted by a high co-solute concentration and low pH. In contrast, gelation of LMP occurs by the formation of ionic linkages via calcium bridges between two carboxyl groups from two different chains in close proximity, known as the ‘egg-box’ model. Pectin gels exhibit Newtonian behaviour at low shear rates and shear-thinning behaviour when the shear rate is increased. An overview of pectin from its origin to its physicochemical properties is presented in this review.